Kajian Etnobotani Loloh dan The Herbal Lokal Sebagai Penunjang Ekonomi Kreatif Masyarakat Desa Tradisional Penglipuran Kabupaten Bangli-Bali - pebiana, ni putu nadia; Puspasari, Yeni Dina; Dewi, Resty Mutiara; Arnyana, Ida Bagus Putu (Jurnal Pendidikan Biologi undiksha, 2020)
Penglipuran Village is a village in Bali that implements ethnobotany which is used as a medicinal plant which has been inherited in the form of a variety of traditional drinks that make use of typical plants in the village and has been widely marketed. The traditional drinks they produce are loloh cem-cem, loloh telang, turmeric loloh, plum fruit loloh and kelor and bawang berlian tea. The purpose of this article is to study the properties needed in plants used as loloh and herbal teas as well as the benefits of ethnobotany loloh and herbal teas as economic support as seen from the level of income of the people involved in their production. The writing of this article was done by taking a sample of snowballs in Penglipuran Village. Data collection techniques used in this study are: observation techniques, interview techniques, literature study techniques and data analysis using descriptive qualitative techniques. Data obtained in the field in accordance with the debates reviewed are described and interpreted qualitatively. The results obtained from this study are some plants that have been produced by economic products that are designed for local drinks, namely loloh and herbal teas. Using plants as traditional medicine by the people of Penglipuran Village, has now developed into an effort that provides economic benefits for the community. Based on the results of the study found three types of local traditional drinks (loloh) that support the welfare and economy of the Penglipuran Traditional Village community namely loloh cemcem, loloh telang flowers, and kelba tea (kelor bawang berlian) seen from the results of production in each transaction and marketing has been quite extensive.